Impact of travel motives on destination choice of mice travelers in southern province - Abeysekara, K.S.; Kulathilaka, C.J.P. (University of Jaffna, 2020)
The number of international tourists is worldwide growing. MICE tourism is an industry that is growing significantly throughout the year. Meeting, Incentive, Convention and Exhibition has emerged as a critical component of the tourism industry. Also, the MICE industry has impacted the global economy by delivering higher income, employment, and government revenue. MICE travellers are identified as people who attend or have attended Meeting, Incentive, Convention and Exhibitions. Travel motives can identify as the factors that influence travellers towards their preferences and also it can refer as a set of needs and wants that influence people to engage with tourism activities. Travel motives are important in understanding and predicting factors that influence travel destinations of MICE travellers and it is one of the internal states that influence travel decision making. It is essential to understand the impact of travel motives when selecting the destinations of MICE travellers. The purpose of this study was examining the relationship between travel motives (push and pull) and destination choice of MICE travellers in Southern Province and identify the impact of travel motives (push and pull) on destination choice of MICE travellers in Southern province. Information about MICE travellers was collected through questionnaires at Southern province in Sri Lanka. A conceptual framework has been developed based on previous researches. The purposive sampling method used to collect data from 100 MICE travellers. The quantitative data analysis method was used in analysing the data using Pearson correlation coefficient and Multiple Leaner Regression. The study results indicated that travel motives (push and pull) are play a positive significant association on destination choice of MICE travellers. Further it reveals that, travel motives (push and pull) significantly impact destination choice of MICE travellers and pull motives are mostly influence on destination choice. The best way is to plan appropriately, improve the quality of the destinations and practice of effective marketing strategies. Future researches can be conducted though examine the domestic tourists and other tourist segments select in Southern province.
Keywords: Destination choice MICE tourism; MICE travellers and travel motives